Face Perception is Whole or None: Disentangling the Role of Spatial Contiguity and Interfeature Distances in the Composite Face Illusion. (October 2013) - Laguesse, Renaud; Rossion, Bruno
Compelling evidence that faces are perceived holistically or configurally comes from the composite face illusion: Identical top halves of a face are perceived as being different if they are aligned with different bottom halves. The visual illusion disappears when the top and bottom face halves are spatially misaligned. Whether this is because the two halves no longer form a whole face (ie they form two segmented parts), or because of an increase in interfeatures distance in the misaligned condition (eg eyes-mouth distance) remains unclear. Here, thirty-four participants performed a delayed matching composite task in which the amount of spatial misalignment between face halves varied parametrically (from 8.33% of face width to 100%). The difference in performance between aligned and misaligned faces (ie the composite face effect) was already of full magnitude at the smallest level of misalignment. These results imply that a small spatial misalignment is sufficient to measure the composite face effect. From a theoretical standpoint, they indicate that it is the breaking of a whole configuration rather than the increase in relative distance between the face parts that explains the presence or absence of the composite face effect, clarifying an outstanding issue concerning the nature of holistic face perception.